Enterprise and entrepreneurship on islands and remote rural environments. (February 2017) - Burnett, Kathryn A; Danson, Mike
Although there has been increasing interest in rural enterprises, relatively little has been written on enterprise and entrepreneurship on islands where problems tend to be different, additional and exaggerated. Economic and cultural development agencies intervene to support such remote and isolated communities but the significance of the dominant metropolitan paradigm in the peripheralization of those establishing and running businesses on islands needs critiqued. This article contrasts experiences but highlights similarities, rather than differences, of rural small and medium enterprises (SMEs) in developing countries and comparative Northern European locations. The key role of social capital, cultural values and norms is analysed and comment presented on small island experiences. Arguments are made for policies to be proofed for locational differences and for further research to understand the opportunities offered by islands and coastal communities in a world where the particularities of place and space are increasingly valued, and aspects of remoteness can be rearticulated to good effect.